The obligate need for accuracy in reporting preclinical studies relevant to clinical trials: autologous germline mitochondrial supplementation for assisted human reproduction as a case study - Jonathan L. Tilly; Dori C. Woods (SAGE Publishing, 2020)
A now large body of work has solidified the central role that mitochondria play in oocyte development, fertilization, and embryogenesis. From these studies, a new technology termed autologous germline mitochondrial energy transfer was developed for improving pregnancy success rates in assisted reproduction. Unlike prior clinical studies that relied on the use of donor, or nonautologous, mitochondria for microinjection into eggs of women with a history of repeated in vitro fertilization failure to enhance pregnancy success, autologous germline mitochondrial energy transfer uses autologous mitochondria collected from oogonial stem cells of the same woman undergoing the fertility treatment. Initial trials of autologous germline mitochondrial energy transfer during - in vitro fertilization at three different sites with a total of 104 patients indicated a benefit of the procedure for improving pregnancy success rates, with the birth of children conceived through the inclusion of autologous germline mitochondrial energy transfer during in vitro fertilization. However, a fourth clinical study, consisting of 57 patients, failed to show a benefit of autologous germline mitochondrial energy transfer- in vitro fertilization versus in vitro fertilization alone for improving cumulative live birth rates. Complicating this area of work further, a recent mouse study, which claimed to test the long-term safety of autologous mitochondrial supplementation during in vitro fertilization, raised concerns over the use of the procedure for reproduction. However, autologous mitochondria were not actually used for preclinical testing in this mouse study. The unwarranted fears that this new study's erroneous conclusions could cause in women who have become pregnant through the use of autologous germline mitochondrial energy transfer during- in vitro fertilization highlight the critical need for accurate reporting of preclinical work that has immediate bearing on human clinical studies.